The Modified Pterional Keyhole Craniotomy for Open Cerebrovascular Surgery: A New Workhorse? - Mocco, J.; Komotar, Ricardo J.; Raper, Daniel M. S.; Kellner, Christopher P.; Connolly, E. Sander; Solomon, Robert A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background The frontotemporal craniotomy is the most commonly used approach for vascular neurosurgery. However, this approach requires significant mobilization of overlying soft tissues, resulting in muscle atrophy and temporomandibular joint pain. We describe a modified pterional keyhole approach and its use in our initial clinical experience.Patients and Methods Eleven consecutive minimally invasive pterional keyhole approaches were used for 14 aneurysms. Patient demographics, aneurysm characteristics, and morbidities were prospectively collected.Results Mean aneurysm size was 6.5 mm, and all were in the anterior circulation. All aneurysms were successfully clipped, with no occurrence of intraoperative rupture or perforator occlusion. There were no incidences of frontalis nerve injury. No technical difficulties or limitation to aneurysm access were experienced.Conclusion In carefully selected patients, a minimally invasive keyhole approach may be a safe and effective alternative to traditional pterional craniotomy for certain anterior circulation aneurysms.
Keywords: keyhole approach; minimally invasive; clipping; intracranial aneurysm; surgery